Characteristics of organic matter-hosted pores in Lower Silurian Longmaxi shale with different maturities, Sichuan Basin - Yunfeng YANG; Fang BAO; Tenger BORJIGIN; Anyang Pan; Baojian SHEN (Shiyou shiyan dizhi, 2020)
Organic matter-hosted pores provide reservoir space and migration pathways for shale gas. The evolution of organic matter-hosted pores (OM pores) of different macerals from Longmaxi shale with a wide variety of thermal maturities has been investigated using field emission scanning electron microscopy (FE-SEM). The Longmaxi shale contains rare graptolites which are the main component of structured organic matter. No OM pores occur in graptolite fragments, irrespective of thermal maturity. OM pores locally developed in graptolite fragments are formed from hydrocarbon generation of organic matter which was replaced by macromolecular material from surrounding sediment or in situ polymerized by lipids from the organism itself. Solid bitumen is not only the major organic component in the Longmaxi shale, but also the main host of OM pore development. The diagenesis of fine-grained sediments and thermal evolution of organic matter have been combined with the morphology of solid bitumen to distinguish pre-oil solid bitumen and post-oil solid bitumen. The post-oil solid bitumen is dominant. The evolution of OM pores within solid bitumen is closely related to thermal maturity. Generally, OM pores within solid bitumen become greater as thermal maturity increases. During the mature to early postmature (GRo < 2.3%) stages, OM pores within solid bitumen are not well developed probably due to the masking by oil and bitumen generated from organic matter. OM pores within solid bitumen are well developed during the late postmature to early overmature (2.3% < GRo < 4.5%) stages, with two main types being spongy and bubble-shaped. For organic-rich Longmaxi shale, the contribution of OM porosity to total porosity is more than 50%. During the late overmature (GRo>4.5%) stage, organic matter carbonization will cause intense damage to shale pores so that the exploration risk of shale gas increases.